Laser texturing of soda lime glass surface for hydrophobic surface in wenzel state - Nur Najwa, Khairul Azman; Najihah, Zanian; Syarifah Nur Aqida, Syed Ahmad; Izwan, Ismail; Salwani, Mohd Salleh (Universiti Malaysia Pahang, 2024)
Glass surfaces tend to be hydrophilic when exposed to water resulting in a low water contact angle and high adhesion. Fabrication on a glass surface with low water adhesion can minimize the droplet’s adhesion conduct self-cleaning, and improve the cleanliness of the glass surface. This paper presents surface texturing of the soda-lime glass surface by laser processing three different patterns to improve water contact angle with low water adhesion on the modified glass surface. A design experiment method was developed to determine the effects of laser parameters on the glass surfaces. The laser parameters used are laser power between 0.45 and 1.05W and scanning speeds of 210, 420, and 600 mm/min. The effects of laser parameters on surface morphology, water contact angle measurement, and average surface roughness, Ra were investigated. The characterization was conducted for surface morphology, two-dimensional surface roughness profile, and water contact angle. The results show that the highest water contact angle obtained after laser texturing is up to 125.29° compared to the as-received surface with a contact angle of 32.35°. The highest water contact angle resulted from 420 mm/min scanning speed and 0.45 W of laser power, responding to the surface with a minimum range of Rax and Ray of 0.96 and 1.5 pm. These findings are significant for designing surface modification of self-cleaning glass surface applications like the automotive windscreens, and window panels for high-rise buildings.